Save our souls : the true story of a castaway family, treachery, and murder - Pearl, Matthew (Harper, an imprint of HarperCollinsPublishers, 2025)
In this true story, on December 10, 1887, the Walker family's shark fishing boat was split in two by a storm, and they awoke in the morning on an island inhabited by a ragged man named Hans who seemed helpful but had a dark secret.